Language learning strategies of Colombian learners of English as a foreign language - Marenco Domínguez, José Miguel; Marín Juanías, José; Molina, Clara (Institute of Advanced Engineering and Science, 2024)
While some studies about language learning strategies (LLS) have been held in Colombia, there is still ample room for research. Particularly, an explanatory sequential mixed methods design can offer insights into how gender, grade level, and perceived language proficiency may influence Colombian students’ selection of strategies for learning English. Furthermore, teachers’ explicit instruction of strategies has not commonly been contrasted with students’ reported use of strategies. This study sought to bridge existing gaps by exploring the favored learning strategies of Colombian learners and teachers at the secondary school level. Data were collected employing the Strategy Inventory for Language Learning and semi-structured interviews with selected participants. The findings suggest that students favor social and metacognitive strategies and use affective strategies to a lesser extent. No significant differences between gender and the overall use of learning strategies were found. Conversely, significant relationships involving students’ grade level, self-perception of English proficiency, and the reported use of LLS were observed. This investigation highlights the importance of boosting affective strategies, exploring teachers’ roles in explicit strategies-based instruction, and integrating diverse types of data to explore the complexity of learning strategies. Recommendations for future inquiries are presented.